DETERMINANTS OF TAX PERFORMANCE IN SELECTED EAST AFRICAN COMMUNITY COUNTRIES - PATRICK MWANZA NZULA (Machakos University Press, 2025)
This study analyzes the determinants of tax performance in Kenya, Tanzania, Rwanda, Uganda, and Burundi from 2013 to 2023. Existing literature shows significant gaps in regional analysis, with most studies focusing on individual countries or other global regions rather than offering a unified empirical examination of tax determinants across EAC nations. Using a fixed effects panel regression model with data from World Development Indicators and International Financial Statistics, the analysis reveals that GDP per capita (β = 3.88, p = 0.002) and manufacturing share (β = 0.16, p = 0.007) are statistically significant drivers of tax ratios. Conversely, variables such as agricultural share, trade openness, financial depth, inflation, and exchange rates were found to be statistically insignificant determinants in this context. Tax effort analysis revealed a universal efficiency gap, with Rwanda (0.91) and Kenya (0.90) demonstrating the highest revenue mobilization efficiency, followed by Uganda (0.87) and Burundi (0.88), while Tanzania (0.77) showed the most significant potential for improvement. The study affirms that sustainable revenue growth in the EAC hinges on long-term structural economic transformation complemented by targeted administrative reforms to bridge the efficiency gap. Recommendations include promoting industrial diversification, enhancing tax administration digitalization, and implementing cooperative taxation models for the agricultural sector. These findings provide evidence-based guidance for policymakers seeking to improve domestic revenue mobilization in line with EAC Vision 2050 and Africa's Agenda 2063 development frameworks.